2019
DOI: 10.1364/oe.27.014487
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of GHz repetition rate fundamentally mode-locked all-fiber lasers

Abstract: GHz repetition rate fundamentally mode-locked lasers have attracted great interest for a variety of scientific and practical applications. A passively mode-locked laser in all-fiber format has the advantages of high stability, maintenance-free operation, super compactness, and reliability. In this paper, we present numerical investigation on passive mode-locking of all-fiber lasers operating at repetition rates of 1-20 GHz. Our calculations show that the reflectivity of the output coupler, the small signal gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…A growing number of scientific and practical applications rely on mode-locked lasers with high peak power sufficient to accomplish the tasks on an ultrashort timescale without inducing any other side effects [5,6]. Passive mode-locking of semiconductor lasers is a very promising method for the generation of low repetition rate picosecond pulses, which is of paramount importance for a number of applications [7]. The passive mode-locked technique, one of commonly used mode-locked techniques, can also be applied on multisection semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of scientific and practical applications rely on mode-locked lasers with high peak power sufficient to accomplish the tasks on an ultrashort timescale without inducing any other side effects [5,6]. Passive mode-locking of semiconductor lasers is a very promising method for the generation of low repetition rate picosecond pulses, which is of paramount importance for a number of applications [7]. The passive mode-locked technique, one of commonly used mode-locked techniques, can also be applied on multisection semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to an error during production, an update to the citations was not made in this paper which has resulted in the citations for references [4][5][6][7][8][9] being misplaced. The second paragraph of the introduction should read as follows:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These properties demonstrate that bismuthene has potential application for spintronics, designing and fabricating room-temperature nondissipative quantum computing devices, ultrafast pulse lasers, and so on. , Ultrashort pulse fiber lasers have also garnered tremendous interest from the researchers because of the compact design structure, low cost, high-efficiency of heat dissipation, and convenient operation. It has been widely applied to many field including materials microprocessing, medicine surgery, and optical fiber telecommunication systems. Huge numbers of materials, such as semiconductor saturable absorber mirrors, graphene, topological insulators, black phosphorus, transition metal dichalcogenides, noble metal nano materials, transition metal chalcogenides, and so on, have been reported to be applied to the generation of ultrashort pulse laser because of its saturable absorption. In addition, broadband, GHz high repetition rate, tunable, and switchable multiwavelength ultrafast fiber lasers also attract further attention because of its potential application in many fields. Moreover, few-layer bismuthene also can be used in the field of ultrafast photonics and nonlinear optics to achieve ultrashort pulse laser. In 2018, Lu et al reported an ultrafast fiber laser with 652-fs optical pulse duration at a center wavelength of 1559.18 nm .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, such lasers do not require periodic polarization adjusting that facilitates their self-starting and increases stability. Fundamentally mode-locked linear cavity fiber lasers with high pulse repetition rates (∼ GHz) are known [13,14]. Their obvious disadvantages arising from their short cavity (∼10 cm) are a small output power, limited tuning options and high requirements for cavity components (mirrors, pump diodes, etc).…”
Section: Introductionmentioning
confidence: 99%